Seasonal availability of bee flora at Coronation Garden, Kirtipur, Nepal (Our Nature, 2025)
This study explores the seasonal availability of bee flora at Coronation Garden, Tribhuvan University, Kirtipur, during 2015-2016. A field survey documented flowering plant species visited by bees, confirming their role as bee flora through visual observations. Identified species were categorized into major, medium, and minor groups based on the nectar and pollen they provided. A total of 197 plant species were identified as bee flora, including horticultural, ornamental, wild, and agricultural species. The spring season of 2016 exhibited the highest abundance of blooming plants, making it the most favourable period for bees. The study emphasizes the importance of seasonal variation in bee flora availability, providing valuable insights for beekeeping practices.